Behavior in preschool children with the 22q11.2 deletion syndrome12. Issue 1 (13th December 2012) - Klaassen, Petra; Duijff, Sasja; Swanenburg de Veye, Henriette; Vorstman, Jacob; Beemer, Frits; Sinnema, Gerben
Abstract Children with the 22q11.2 deletion syndrome (22q11DS) are at an increased risk of psychiatric problems from pre‐adolescence; little is known, however, about behavioral problems at a preschool age and the relationship between speech and behavior in this group. Parents of 90 children (aged 1.42–5.99 years) with 22q11DS filled out the Child Behavior Checklist, documenting behaviors including speech problems. Their profiles were compared with those of a comparison group consisting of 33 children with nonsyndromic orofacial clefts without 22q11DS, since both children with 22q11DS and children with clefts are expected to have speech problems. In the 22q11DS group, data on intelligence was acquired by means of formal tests. Parents of children with 22q11DS reported significantly higher mean scores on withdrawn behavior, affective problems and pervasive developmental problems compared to children with nonsyndromic clefts. Approximately 30% of children with 22q11DS had a score above the 97th percentile on at least one of the behavior subscales, indicating psychopathology. In children with 22q11DS, the reported behavioral problems were not associated with speech problems. Behavioral problems were found in 30% of young children with 22q11DS and were unlikely to be caused by speech problems. Within the 22q11DS group, behavioral problems were not related to the degree of cognitive impairment. This shows that many children with 22q11DS, known to be at an increased risk of psychiatric problems from pre‐adolescence, already show behavioral problems before the age of 6 years. © 2012 Wiley Periodicals, Inc.